Pengaruh Strategi Pemasaran Syariah, Kepuasan Konsumen, dan Kepercayaan Konsumen Terhadap Loyalitas Konsumen (Studi Kasus Pada Naughti Hijab Store) - Sumadi Sumadi; Muhammad Tho’in; Tino Feri Efendi; Diyah Permatasari (ITB AAS INDONESIA Surakarta, 2021)
This study aims to find evidence of the influence of Sharia Marketing Strategy, Consumer Satisfaction, and Consumer Confidence. This type of research is quantitative research. The population in this study are consumers at Naughti Hijab Store. The sampling technique used is using the Slovin formula. The sample in this study in this amounted to 100 respondents Naughti Hijab Store cunsumers. In this study using four variables, namely sharia marketing strategy, consumer satisfaction, and consumer confidence as independent variables and consumer loyalty as the dependent variable. This study uses multiple linear regression analysis method with the help of SPSS. The results showed that the sharia marketing strategy had a positive and significant effect on consumer loyalty, consumer satisfaction did not have a positive and significant effect on consumer loyalty, and consumer confidence had a positive and significant effect on consumer loyalty. From the results of multiple linear regression analysis, the coefficient of each variable is obtained, namely sharia marketing strategy 0,000, consumer satisfaction at 0.081, and consumer confidence at 0,016.